Quantum cloaking of a hard sphere - Blancas, Philip Jordan D.; Galapon, Eric A. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2014)
Quantum cloaking of a hard sphere is studied in the small energy limit. The hard sphere is coated with the potential coating shells that functions as an invisibility cloak from quantum particles. In the first part of this thesis, quantum cloaking of a hard sphere using a single potential shell is examined. The potential strength Vo that is considered in the first part is less than the energy of the incident particle E, Vo<E. The quantum cloaking effect of a hard sphere if Vo is positive or negative is shown. It is shown that the cloaking of the hard sphere happens when it is coated by a negative single coat. In the second part of this thesis the quantum cloaking effect of a hard sphere is presented if it is coated using a single potential shell in which Vo>E. It is shown in this part that there are allowed combination between the coating thickness and the potential strength in order to cloak a hard sphere. In the penutimate part of this thesis, the total scattering cross-section of the hard sphere is obtained if it is coated by double and triple positive potential shells. The potential strengths of the said potential coats are all less than the energy of the incident article. As a result, the total scatering cross-section of the positive multi-layered coated hard sphere is greater than the total scattering cross-section of the positive single coated hard sphere. And in the last part of this thesis, the preferred chirality to enhance the cloaking of a hard sphere is revealed. It is shown in this part that the hard sphere can be cloaked more if it is struck by the left handed incident particles.
Thesis (Master of Science-Physics)--University of the Philippines Diliman
Keywords: Quantum solids